LANGUAGE PRESERVATION EFFORTS IN THE AGE OF GLOBALIZATION - Choriyeva Mohina Hakim qizi (Western European Studies, 2025)
With the increasingly globalized world, the globalization process poses fundamental challenges to language diversity and conservation against dying languages. This article examines worldwide language conservation efforts with an emphasis on best practices, bottom-up initiatives, and technological interventions to safeguard linguistic heritage. From the analysis of case studies and actions of various communities, the article identifies linguistic diversity as an important element of cultural identity as well as social resilience. It informs that the preservation of languages not only maintains heritage but also cultivates the wealth of world culture and enables sustainable communication strategies.
Keywords: language preservation; globalization; linguistic diversity